2004
DOI: 10.1128/mcb.24.16.7260-7274.2004
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens and Progesterone Promote Persistent CCND1 Gene Activation during G1 by Inducing Transcriptional Derepression via c-Jun/c-Fos/Estrogen Receptor (Progesterone Receptor) Complex Assembly to a Distal Regulatory Element and Recruitment of Cyclin D1 to Its Own Gene Promoter

Abstract: Transcriptional activation of the cyclin D1 gene (CCND1) plays a pivotal role in G 1 -phase progression, which is thereby controlled by multiple regulatory factors, including nuclear receptors (NRs). Appropriate CCND1 gene activity is essential for normal development and physiology of the mammary gland, where it is regulated by ovarian steroids through a mechanism(s) that is not fully elucidated. We report here that CCND1 promoter activation by estrogens in human breast cancer cells is mediated by recruitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(133 citation statements)
references
References 70 publications
5
127
0
1
Order By: Relevance
“…Inside the region located between nucleotides (nt) Ϫ737/ Ϫ730 (distal) or between nt Ϫ143/Ϫ133 (proximal), there are elements recognized by the transcription factors of the E2F family (Fukami-Kobayashi and Mitsui, 1998;Watanabe et al, 1998;Cicatiello et al, 2004). Because ChIP assays (Cicatiello et al, 2004) have revealed that E2F factors bind to DNA in a cell cycle progression-related manner, we next performed deletions of the E2F region, and we designed functional assays to test the particular relevance of these transcription factors in controlling the cyclin D1 promoter activity under ZO-2 effect.…”
Section: Zo-2 Repression Is Mediated By a Putative E2f/e Box Located mentioning
confidence: 99%
See 2 more Smart Citations
“…Inside the region located between nucleotides (nt) Ϫ737/ Ϫ730 (distal) or between nt Ϫ143/Ϫ133 (proximal), there are elements recognized by the transcription factors of the E2F family (Fukami-Kobayashi and Mitsui, 1998;Watanabe et al, 1998;Cicatiello et al, 2004). Because ChIP assays (Cicatiello et al, 2004) have revealed that E2F factors bind to DNA in a cell cycle progression-related manner, we next performed deletions of the E2F region, and we designed functional assays to test the particular relevance of these transcription factors in controlling the cyclin D1 promoter activity under ZO-2 effect.…”
Section: Zo-2 Repression Is Mediated By a Putative E2f/e Box Located mentioning
confidence: 99%
“…The pXP2-CD1 reporter vector contains the cyclin D1 regulatory region here shown. TRE(AP-1), TRE, Ϫ924 to Ϫ938 (Herber et al, 1994); dE2F, distal E2F, Ϫ730 to Ϫ737 (Herber et al, 1994); E box, bHLH, and Zn finger transcription factors binding site, Ϫ547 to Ϫ553 (Herber et al, 1994); ZONAB, ZONAB binding site and inverted CCAAT box, Ϫ527 to Ϫ532 (Sourisseau et al, 2006); Oct, Oct binding site, Ϫ646 to Ϫ652 (Cicatiello et al, 2004); pE2F, proximal E2F, Ϫ133 to Ϫ143 (Watanabe et al, 1998); Tcf/Lef, Tcf/Lef binding site, Ϫ67 to Ϫ77 (Shtutman et al, 1999); CRE, Ϫ46 to Ϫ53, (Herber et al, 1994); and Start, site of transcription initiation, Ϫ1/ϩ1 (Herber et al, 1994). Broken arrow stands for the transcription start point.…”
Section: Zo-2 Down-regulates Cyclin D1 Transcription and Protein Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among estrogens, 17-b estradiol is the major promoter of cell proliferation in both normal and neoplastic breast tissue through its binding to the highaffinity estrogen receptor (ERa). ERa functions as an estrogen-activated transcription factor and mediates the expression of target genes involved in the regulation of cell proliferation and inhibition of apoptosis of the breast epithelium (Cicatiello et al, 2004;Helguero et al, 2005). Excessive activation of the ERa pathway due to increased hormonal secretion, prolonged estrogen exposure or increased levels of the receptor may lead to increased risk to develop breast cancer (Calaf, 2006;Lee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Transient transfection-based studies have mapped several potential estrogen-responsive sites in the CCND1 proximal promoter, including an atypical cyclic AMP response element (position −57), an AP1 site (position −954), and GCrich sites (positions −110 and −143) (Altucci et al 1996;Sabbah et al 1999;Castro-Rivera et al 2001;Liu et al 2002;Park et al 2005). Stable integration of reporter constructs in BCC was recently used by Cicatiello et al (2004) to show that in this context estrogen stimulation required primarily the AP1 site. These authors proposed that ER␣ loading at the CCND1 promoter upon estrogen stimulation was mediated through interaction with AP1, resulting in the assembly of an activator complex responsible for CCND1 transcriptional induction.…”
mentioning
confidence: 99%